Optimism vs. pessimism: Exploring the dual realities of WFH among EFL tertiary learners during the COVID-19 pandemic - Pammu, Abidin; Hamuddin, Budianto (International Journal of Innovative Research and Scientific Studies, 2024)
This study focuses on English as Foreign Language (EFL) students at Hasanuddin University, Makassar, to explore the effects of the shift to Working from Home (WFH) learning. The COVID-19 pandemic has drastically altered the educational landscape, especially in higher education. It aims to understand the psychological impact and the range of attitudes towards this new mode of learning among EFL students. This research involved students from two cohorts (2020 and 2021). A sample of 60 participants was chosen to complete an online perception questionnaire distributed via Google Forms. The study employed content analysis within an interpretative paradigm to analyze the responses. Analysis of the data revealed a dichotomy in student perspectives, categorizing them as "optimisms" and "pessimisms" based on their attitudes towards WFH learning. The findings highlighted a variety of psychological impacts experienced by the students, encompassing both negative and positive aspects. The results indicate significant implications for EFL educators. They suggest a need for increased focus on online pedagogical methods and emphasize the importance of adaptability, flexibility, and productivity in the evolving educational environment. The study also sheds light on the diverse psychological experiences of students, underscoring the need for educational strategies that cater to these varied needs. This study provides critical insights into the perceptions and psychological impacts of WFH learning on EFL students at Hasanuddin University. It underscores the challenges and opportunities presented by the transition to online learning, offering valuable guidance for educators in similar contexts.